Mass Spectrometry-Based Lipidomics Reveals Differential Changes in the Accumulated Lipid Classes in Chronic Kidney Disease - Marczak, Lukasz; Idkowiak, Jakub; Tracz, Joanna; Stobiecki, Maciej; Perek, Bartłomiej; Kostka-Jeziorny, Katarzyna; Tykarski, Andrzej; Wanic-Kossowska, Maria; Borowski, Marcin; Osuch, Marcin; Formanowicz, Dorota; Luczak, Magdalena (Metabolites, 2021)
Chronic kidney disease (CKD) is characterized by the progressive loss of functional nephrons. Although cardiovascular disease (CVD) complications and atherosclerosis are the leading causes of morbidity and mortality in CKD, the mechanism by which the progression of CVD accelerates remains unclear. To reveal the molecular mechanisms associated with atherosclerosis linked to CKD, we applied a shotgun lipidomics approach fortified with standard laboratory analytical methods and gas chromatography-mass spectrometry technique on selected lipid components and precursors to analyze the plasma lipidome in CKD and classical CVD patients. The MS-based lipidome profiling revealed the upregulation of triacylglycerols in CKD and downregulation of cholesterol/cholesteryl esters, sphingomyelins, phosphatidylcholines, phosphatidylethanolamines and ceramides as compared to CVD group and controls. We have further observed a decreased abundance of seven fatty acids in CKD with strong inter-correlation. In contrast, the level of glycerol was elevated in CKD in comparison to all analyzed groups. Our results revealed the putative existence of a functional causative link-the low cholesterol level correlated with lower estimated glomerular filtration rate and kidney dysfunction that supports the postulated "reverse epidemiology" theory and suggest that the lipidomic background of atherosclerosis-related to CKD is unique and might be associated with other cellular factors, i.e., inflammation.
Keywords: lipidomics; cardiovascular disease; mass spectrometry; lipid profiling; chronic kidney disease